Strategies for Improving Production Quality in the Context of Product Transition in the Paper Manufacturing Industry - Findra Ahmad Falsafi; Putu Dana Karningsih (Eduvest - Journal of Universal Studies, 2026)
Digital disruption has shifted global paper demand, reduced graphic paper consumption while increased packaging paper demand due to e-commerce growth. In response, a paper manufacturer converted one machine line (PM1) from newsprint to 50-gsm recycled-fiber packaging paper. Post-conversion, PM1 experienced non-salable output exceeding the 8% quality threshold, with three dominant defects accounting for 80.2% of occurrences (Pareto) and generating internal failure costs of IDR 4.39 billion in losses. The objective of this research is to determine the current baseline using Defect Per Million Opportunity (DPMO) and sigma level measurements and to address the elevated dominant defects. The study proposes a quality improvement framework that integrates Six Sigma–DMAIC with a Quality Improvement Matrix (QIM), primarily to map initial performance, identify the root causes of defects, and prioritize improvement actions by considering their effectiveness and implementation difficulty. From the implementation of the method, 14 alternative improvement actions were identified, which were then prioritized, resulting in 11 priority actions being implemented in the company. The results showed that the baseline process (prior to improvement) had a DPMO of 23,818 and a sigma level of 3.49. After the improvements were implemented, dominant defects related to colored spots, holes, and paper strength issue decreased by 88%, 61%, and 77%, respectively; the total broke percentage declined from 18.23% to 6.05%; DPMO decreased to 12,051; the sigma level increased to 3.82. These findings indicate that the integration of Six Sigma-DMAIC and the Quality Improvement Matrix was effective in improving the quality of PM1 production after conversion.